Harmonizing Online Business and Tax Compliance: A Comprehensive Analysis - Noviana Archintya; Noor Fatimah Mediawati; Pristiwanto (Proceedings of The ICECRS, 2023)
This data article aims to quantify the extent of scholarly literature addressing the nexus of Online Business and Tax Compliance. Leveraging the Lens.org platform, we conducted a keyword search for "Online Business AND Tax Compliance," resulting in a total of 10,180 documents. Employing filters for Document Types (Journal Article and Conference Proceedings) and Subject Matter (Law), we refined the dataset to 509 documents. This dataset facilitates comprehensive research on the intersection of online business operations and tax compliance, offering valuable insights and resources for scholars and researchers in the field.Highlights: Extensive Dataset: This data article provides access to a substantial dataset of 509 journal articles and conference proceedings, offering researchers a comprehensive resource for in-depth exploration of the relationship between online business and tax compliance. Streamlined Research: Researchers can efficiently access and analyze this data, streamlining their efforts in the study of online business tax compliance, thanks to the carefully curated filters and export options. Foundational Research Tool: The dataset serves as a foundational research tool, enabling scholars and scientists worldwide to examine the dynamics of online business and tax compliance, potentially leading to improved compliance practices and a better understanding of this critical intersection. Keywords: Online Business, Tax Compliance, Data Analysis, Scholarly Literature, Legal Research